INHERITANCE RIGHTS: DIFFERENCES BETWEEN BOYS AND GIRLS FROM AN ISLAMIC LAW PERSPECTIVE - Harisman, Harisman (Proceeding International Seminar of Islamic Studies, 2024)
This discussion aims to find out and analyze what is the basis for consideration of the Qur'an on the difference in inheritance rights for boys and girls with a ratio of 2:1. Moreover, this issue received different responses from various groups. Some are of the view that the division of inheritance rights like this does not provide a sense of justice and even considers it to be discriminatory, especially for girls. For this reason, it is considered important to conduct normative research using a normative juridical approach that refers to the provisions contained in the Qur'an, hadith and compilations of Islamic law obtained through literature or literature studies. The data used in this study is secondary data obtained from the literature. To answer this question, a qualitative analysis was carried out on the secondary data that had been collected and then the results were described. Based on the analysis, it was found that there are several basic considerations for the differences in the share of inheritance rights between boys and girls, namely: first: to raise the status of girls to be equal to boys in obtaining inheritance rights to inheritance from their parents. Second: the obligations of boys are heavier than girls, because men provide for their wives and children, pay dowries, and even take care of their parents after marriage. Third: to emphasize the part of the girls make it a measure for boys.